The Challenge of Terrorism and War on Terror: Chinese Response - Khalid Rahman (Policy Perspectives, 2012)
[The world, including the US itself, has borne a very heavy cost of the 'War on Terror' (WoT) - now running for over a decade while the gains are negligible. Even the objectives stated by the US itself remain far from achieved. As WoT was being launched; China was faced with four options: i) all out support, ii) conditional support iii) tacit endorsement and, iv) political support for anti-terrorism measures. However, China remained cautious towards use of force. Chinese perspective of international terrorism, while focusing on the origin and evolution also seeks to address the root causes and the links to international political, economic, and social justice. China, along with expressing its principal stand has taken part in WoT in such a way that it has not played any role in the social, human, economic and environmental destructions caused by the war. Efforts to strike a balance between immediate and long term policy objectives in Chinese approach with regard to response to WoT seem continuing. Setting aside China's own national interests, Beijing's policy has not helped much in genuinely dealing with the problem of terrorism, addressing its root causes and moving towards a just global system. While terrorism should not be acceptable in any form, there is a need to define various forms of it. A just and participatory global system has to be ensured; and considering China has eminence at global level, it is all but natural to expect from the country that it will lead the way towards this much need change, at conceptual and operational levels.]